Tropisetron attenuated the anxiogenic effects of social isolation by modulating nitrergic system and mitochondrial function - Amiri, Shayan; Amini-Khoei, Hossein; Haj-Mirzaian, Arya; Rahimi-Balaei, Maryam; Naserzadeh, Parvaneh; Dehpour, AhmadReza; Mehr, Shahram Ejtemaei; Hosseini, Mir-Jamal (Biochimica et biophysica acta, 2015)
Early social isolation stress (SIS) is associated with the occurrence of anxiety behaviors. It seems interaction between the nitrergic system and mitochondrial function plays a role in mediating the anxiety-like behaviors. In this study, we aimed to investigate the anxiolytic effects of tropisetron in animal model of SIS and we try to illustrate the possible role of nitrergic system and mitochondrial function. We applied early social isolation paradigm to male NMRI mice. Animals treated with various doses of tropisetron, nitric oxide agents or their combination and anxiety-like behaviors of animals were assessed using valid behavioral tests including elevated plus maze (EPM), open-field test (OFT) and hole-board test (HBT) in their adulthood. Effects of housing conditions and drug treatments on the mitochondrial function were investigated in the hippocampus by assessing the ATP, GSH, ROS and nitrite levels. Anxiogenic effects of early SIS were assessed in the EPM, OFT, and HBT. Also, SIS disrupted mitochondrial function and caused oxidative stress in the hippocampus of stressed animals. Tropisetron showed an anxiolytic effect in the stressed mice. Also, these effects were mediated by nitrergic system by affecting mitochondrial function and modulating the oxidative stress. L-arginine, a nitric oxide precursor, abolished the anxiolytic effects of tropisetron in the behavioral tasks and blocked the protective effects of it against mitochondrial and oxidative challenge. Our results demonstrated tropisetron attenuated the anxiogenic effects of SIS by mitigation of the negative effects of nitric oxide on mitochondrial function. •Early SIS induced anxiety-like behaviors in the adult socially isolated mice.•Early SIS induced mitochondrial dysfunction and oxidative stress in hippocampus.•Aminoguanidine and L-NAME reversed the anxiogenic effects of early SIS.•Tropisetron alleviated SIS-induced anxiety and mitochondrial function.•Tropisetron improved mitochondrial function and behavior by regulating iNOS.